Three-loop quark form factor at high energy: the leading mass corrections - Liu, Tao; Penin, Alexander A.; Zerf, Nikolai (Physics letters, 2017)
We compute the leading mass corrections to the high-energy behavior of the massive quark vector form factor to three loops in QCD in the double-logarithmic approximation.